2020
DOI: 10.1111/cts.12793
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Natural Growth of Two Strains of Mycobacterium Marinum for Translational Antituberculosis Drug Development

Abstract: The zebrafish infected with Mycobacterium marinum (M. marinum) is an attractive tuberculosis disease model, showing similar pathogenesis to Mycobacterium tuberculosis (M. tuberculosis) infections in humans. To translate pharmacological findings from this disease model to higher vertebrates, a quantitative understanding of the natural growth of M. marinum in comparison to the natural growth of M. tuberculosis is essential. Here, the natural growth of two strains of M. marinum, E11 and M USA , is studied over an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…The drug responses of isoniazid, rifampicin and ethambutol have been quantified on these states (Clewe, Aulin, Hu, Coates, & Simonsson, 2016) and successfully translated to mice (Chen et al, 2017) and patients (Clewe et al, 2018;Svensson & Simonsson, 2016). This multistate approach, especially when the in vitro natural growth and time-kill is repeated for M. marinum as well, can be integrated with our analysis of M. marinum to strengthen the translational value of findings in zebrafish to higher vertebrates (Van Wijk, Van der Sar, et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The drug responses of isoniazid, rifampicin and ethambutol have been quantified on these states (Clewe, Aulin, Hu, Coates, & Simonsson, 2016) and successfully translated to mice (Chen et al, 2017) and patients (Clewe et al, 2018;Svensson & Simonsson, 2016). This multistate approach, especially when the in vitro natural growth and time-kill is repeated for M. marinum as well, can be integrated with our analysis of M. marinum to strengthen the translational value of findings in zebrafish to higher vertebrates (Van Wijk, Van der Sar, et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Assaying internal concentrations can provide valuable information on calculating various pharmacokinetic parameters to further translate drug screening findings to humans ( Rennekamp and Peterson, 2015 ; Yadav et al, 2021 ). In particular, methods for nanoscale blood sampling in zebrafish larvae and pharmacokinetic-pharmacodynamic modeling demonstrated that the larval zebrafish response to an anti-tuberculosis drug could be translated to known effects in humans ( Van Wijk et al, 2020 ). Despite these advances, measuring the biodistribution of compounds to specific organ systems in zebrafish embryos and larvae is difficult.…”
Section: Drug Pharmacology and Chemistry Considerationsmentioning
confidence: 99%
“…Similarly, two patients infected with the same strain can have different susceptibility to the same antibiotic because of differences in immunity [ 140 ]. It is therefore recommended to validate drug susceptibilities in a panel of NTM isolates to increase the chances of selecting strains with the closest growth profile as the isolate of interest [ 131 , 141 ].…”
Section: Models For Drug Discovery Against Ntmmentioning
confidence: 99%